A COMPARATIVE ANALYSIS OF INTERNATIONAL ENGLISH LANGUAGE EXAMS AND THEIR IMPACT ON ENGLISH LANGUAGE TEACHING - Mamaraimovna , Tilavova Malika (Educational Research in Universal Sciences, 2024)
In this scientific article provides an overview and comparative analysis of the types of international English language tests and their impact on English language teaching. International English language tests such as TOEFL, IELTS and Cambridge English Language Tests have a significant impact on English language teaching, as highlighted in this article. The fact that these exams serve as a standardized assessment of students’ language proficiency and are widely accepted by educational institutions, employers, and immigration authorities around the world is detailed in this article.